Psychological characteristics of aggressiveness in adolescence (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the problems of aggressive behaviorin adolescence. The relevance of her research in the context of globalsocial transformations is noted. Some approaches to the interpretationof a certain concept are considered. An attempt is made to systematizethe leading factors of adolescent aggressiveness. The role of the referenceenvironment and family education as possible catalysts of aggressivenessat this age is noted. The specifics of teenage aggression in connectionwith the age crisis and the processes of intensification of self-awarenessare revealed. Typologies and classifications of aggressiveness are presented,some characterological characteristics of the personality of an aggressiveteenager are highlighted.
Keywords: aggressiveness; aggressive behavior; self-awareness; reference environmen; amily relationships